"Stuck in the Middle with You?" Supervisory Level and Anger about Work. (10th August 2017) - Magee, William; Upenieks, Laura
Abstract : Although sociologists have long been interested in the stratification of emotions, the occupational stratification of anger has been investigated in only a few general population studies. Through analyses of data representative of workers in Toronto, we evaluate the hypothesis that workplace hierarchical position, defined by supervisory level, has an inverted u‐shaped association with the frequency of anger about work. We also evaluate the more specific hypothesis that the difference in work‐related anger between front‐line supervisors and nonsupervisory workers will be relatively larger among workers in the commodified services sector than other sectors. Results are generally consistent with our hypotheses. We find that both front‐line supervisors in the commodified services sector, and secondary supervisors in all employment sectors, report more frequent anger about work than do nonsupervisory workers. In contrast, higher level supervisors report anger about work at about the same frequency as nonsupervisory workers. These associations are only slightly reduced by controls for work stress and stressors. We discuss how supervisory relations might explain differences in anger about work among workers at different levels in organizational hierarchies.